THE EDUCATIONAL POLICIES FOR SAFEGUARDING AND TRANSMITTING THE LANGUAGE AS AN INTANGIBLE CULTURAL HERITAGE - Tvaltvadze, Darejan; Gvelesiani, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Nowadays, almost all states of the world recognize the importance of the protection of cultural and language rights in sustainability of communities. This attitude is directed by globalizing processes, which strive to transform the world into a single entity via reducing differences. On the background of the globally-determined reformation, preservation of languages, traditions, values and other aspects of culture acquires the greatest urgency. Therefore, states have to pay a special attention to the protection of rights of ethnic, religious and linguistic minorities. The paper deals with the presentation of the progressive state policies as well as the projects/programs facilitating the integration of the ethnic minorities into the Georgian society with the emphasis on the general and higher education. The projects/programs aim at teaching the state language to those representatives of ethnic minorities, who have a poor knowledge or no knowledge of the Georgian language. Determination of the major challenges and outcomes of the projects/programs, discussion of some gaps, introduction of convenient opportunities of their “filling” - these are the major issues of the paper. The methodology of research includes observation, analysis and evaluation of the ongoing processes.